2018
DOI: 10.1016/j.cognition.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Inferring causes during speech perception

Abstract: One of the central challenges in speech perception is the lack of invariance: talkers differ in how they map words onto the speech signal. Previous work has shown that one mechanism by which listeners overcome this variability is adaptation. However, talkers differ in how they pronounce words for a number of reasons, ranging from more permanent, characteristic factors such as having a foreign accent, to more temporary, incidental factors, such as speaking with a pen in the mouth. One challenge for listeners is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 46 publications
(136 reference statements)
11
67
2
Order By: Relevance
“…The adaptation additionally began to fade over time: The magnitude of adaptation (in conditions in which it was present) was larger in the first half of testing than in the second half of testing (see the Supplemental Material for additional visualizations). This reduction in the adaptation effect over time is in line with previous findings (Liu & Jaeger, 2018) and is perhaps not surprising given the remarkably limited sample during exposure (only 22 edited tokens out of 142 total) and the comparatively long testing phase.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The adaptation additionally began to fade over time: The magnitude of adaptation (in conditions in which it was present) was larger in the first half of testing than in the second half of testing (see the Supplemental Material for additional visualizations). This reduction in the adaptation effect over time is in line with previous findings (Liu & Jaeger, 2018) and is perhaps not surprising given the remarkably limited sample during exposure (only 22 edited tokens out of 142 total) and the comparatively long testing phase.…”
Section: Resultssupporting
confidence: 91%
“…The independent variables were experimental condition: shifted phone (shifted /t/ vs. shifted /d/, sum-coded), timing (text before and text after, sum-coded), and their interaction. VOT (continuous variable, scaled and centered) and test half (first vs. second, sum-coded) were included as main effects and interaction terms with experimental conditions to test whether the effects of interest changed over the course of the test phase; this followed previous observations (e.g., Liu & Jaeger, 2018) that perceptual adaptations may be unlearned, to some degree, throughout testing. We attempted to include block number (1 to 9, centered) as a factor, but no models with this factor converged, so we used test half (first four blocks vs. last five blocks) instead.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that despite this variability, web-based experiments on speech perception are feasible [ 45 – 47 ]. This includes studies on accent adaptation [ 48 50 ]. To reduce the between-speaker variability, we required participants to use either in-ear or over-ear headphones when taking the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…When the idiosyncrasy is likely attributable to the speaker, listeners would develop a speaker-dependent expectation for the subsequent input. Alternatively, when an unexpected input is likely caused by an incidental factor, it would not be expected to recur once the cause is removed [ 79 , 80 ]. Contextually modulated interpretations of disfluencies (e.g., ‘Click on [pause] thee uh…”) have also been discussed under this model [ 25 , 26 , 81 ].…”
Section: Discussionmentioning
confidence: 99%